The Factors Influencing the Internet Addiction of Secondary Education Students - (:unkn) unknown (ANI YAYINCILIK, 2013)
Problem Statement: The problem of this study is determined as the impact of genders and family functions of secondary education students on their internet addiction levels. Study has also analyzed whether socio-economic situations and the usage of internet influence internet addiction of adolescents. The Purpose of the Study: The purpose of the study is t*o determine the effect of the genders and family functions of secondary education students on their internet addiction, and to investigate the relationship of such variables as daily internet usage durations, perceived socio-economic levels, and grades with internet addiction. Method: This is a descriptive study. The research universe consists of two secondary schools located in Beyoglu district of Istanbul province. Random sampling and convenience sampling methods were employed. The sample includes 315 students. 171 are female, and 144 are male. Internet addiction scale and family evaluation scale were used. Hierarchical regression analysis and Kruskal Wallis test were carried out. Findings and results: At the first stage, the variable of gender was put into analysis as a predictor of internet addiction. It explained 1.2% of total variance. At the second stage, the variable of family functions were analyzed and seen to have an additional contribution of 11.8%. The variables of gender and family functions explain collectively 13.4% of the variance pertaining to internet addiction. Family functions rank first as the most important predictor of family functions (with the sub-dimensions of behavioral control, affective responsiveness, and affective involvement in the order of importance) while the variable of gender comes second in this matter. Conclusions and Recommendations: Within the context of this study; behavioral control, emotional responding, showing the needed care, gender variables and sub dimensions are family roles influencing internet addiction even though their effects are low. Furthermore it is possible to imply that internet addiction risk is increased by the development of socio-economic status and the increment of time spent on internet.
Keywords: Internet; internet addiction; family function; DISORDER; MODEL